Duloxetine-Induced Hyponatremia in an Elderly Male Patient with Treatment-Refractory Major Depressive Disorder - Ching-Fang Sun; Yeo-Lin Chen; Ying-Hsuan Li; Monika Kumaraswamy; Ying-Chih Lo; Yi-Ting Chen (Case Reports in Psychiatry)
Several classes of antidepressants can induce syndrome of inappropriate antidiuretic hormone hypersecretion (SIADH), thereby causing hyponatremia. Initial symptoms of hyponatremia include neuropsychiatric and gastrointestinal manifestations can mimic depression, especially in elderly people with multiple somatic complaints. Here we present a case of a 68-year-old man with treatment-refractory depression and general anxiety disorder who developed duloxetine-induced hyponatremia. His symptoms of hyponatremia including unsteady gait, dizziness, nausea, general malaise, and poor appetite subsided after discontinuing the offending medication. Our case illustrates that drug-induced SIADH and potential drug-drug interactions should be considered in elderly patients who develop hyponatremia following the initiation of antidepressants.